Australia and New Zealand - Lindop, Christine (Oxford University Press, 1998)
Where would you go to see a platypus? What is Uluru? Who was Ned Kelly? And where can you find a city built on forty-eight volcanoes? The answers to all these questions, and many more, are here. This book looks at life in modern Australia and New Zealand, at the geography and history of these two fascinating countries, and at their growing importance in the world of the future